Dyspnea in COPD: New Mechanistic Insights and Management Implications - O’Donnell, Denis E. (Adv Ther, 2019)
Dyspnea is the most common symptom experienced by patients with chronic obstructive pulmonary disease (COPD). To avoid exertional dyspnea, many patients adopt a sedentary lifestyle which predictably leads to extensive skeletal muscle deconditioning, social isolation, and its negative psychological sequalae. This “dyspnea spiral” is well documented and it is no surprise that alleviation of this distressing symptom has become a key objective highlighted across COPD guidelines. In reality, this important goal is often difficult to achieve, and successful symptom management awaits a clearer understanding of the underlying mechanisms of dyspnea and how these can be therapeutically manipulated for the patients’ benefit. Current theoretical constructs of the origins of activity-related dyspnea generally endorse the classical demand–capacity imbalance theory. Thus, it is believed that disruption of the normally harmonious relationship between inspiratory neural drive (IND) to breathe and the simultaneous dynamic response of the respiratory system fundamentally shapes the expression of respiratory discomfort in COPD. Sadly, the symptom of dyspnea cannot be eliminated in patients with advanced COPD with relatively fixed pathophysiological impairment. However, there is evidence that effective symptom palliation is possible for many. Interventions that reduce IND, without compromising alveolar ventilation (V(A)), or that improve respiratory mechanics and muscle function, or that address the affective dimension, achieve measurable benefits. A common final pathway of dyspnea relief and improved exercise tolerance across the range of therapeutic interventions (bronchodilators, exercise training, ambulatory oxygen, inspiratory muscle training, and opiate medications) is reduced neuromechanical dissociation of the respiratory system. These interventions, singly and in combination, partially restore more harmonious matching of excessive IND to ventilatory output achieved. In this review we propose, on the basis of a thorough review of the recent literature, that effective dyspnea amelioration requires combined interventions and a structured multidisciplinary approach, carefully tailored to meet the specific needs of the individual.